Encoding/decoding, the transmission model and a court of law. (January 2016) - Tomaselli, Keyan
Stuart Hall's encoding/decoding model is discussed in terms of C.S. Peirce's theory of the interpreter and interpretant. This historical semiotic window frames an example to which the Hall model was applied in South Africa to oppose a military dirty tricks campaign that involved a Supreme Court case brought against the Minister of Defence by the End Conscription Campaign requiring him to cease his disinformation against the ECC. The minister's own expert had proposed a transmission model of communication that was defeated by the Peirce-Hall combination. The author argues that the model can be massively strengthened when combined with Peirceian semiotics.